Knowledge and Compliance of COVID-19 Health Protocols among Pregnant Women in Urban and Rural West Java Province - Amir Syafruddin; Tria Astika Endah Permatasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Pregnant women are a risk group for exposure to infectious diseases, especially COVID-19. The study aimed to analyze the relationship between knowledge and compliance with health protocols for preventing COVID-19 in pregnant women in urban and rural areas in West Province, Indonesia. A cross-sectional design on 414 pregnant women in Bekasi Regency representing urban, and Bekasi City representing rural West Java Province in May-July 2021. The sample was selected by random sampling technique. Data were taken through direct interviews using a questionnaire and analyzed using bivariate analysis with SPSS Version 22.0. Pregnant women who comply with health protocols for preventing COVID-19 in urban and rural areas are 91.8% and 89.4%, respectively. Pregnant women who have good knowledge about the prevention of COVID-19 disease in urban and rural areas are 54.1% and 60.4%, respectively. Knowledge is related to the compliance of pregnant women in urban areas (p=0.020; OR:0.23; 95% CI:0.06-0.82). Whereas in rural areas, knowledge is not related to the compliance of pregnant women (p more than 0.05). Socialization regarding the importance of complying with health protocols still needs to be carried out to prevent exposure to infectious diseases, especially COVID-19.Abstrak: Ibu hamil merupakan kelompok berisiko untuk terpapar penyakit infeksi terutama COVID-19. Tujuan penelitian adalah menganalisis hubungan pengetahuan terhadap kepatuhan protokol kesehatan pencegahan COVID-19 pada ibu hamil di wilayah urban dan rural di Provinsi Jawa Barat, Indonesia. Desain cross-sectional dilakukan pada 414 ibu hamil di Kabupaten Bekasi mewakili wilayah urban, dan Kota Bekasi mewakili wilayah rural Provinsi Jawa Barat pada Mei-Juli 2021. Sampel dipilih dengan teknik random sampling. Data diambil melalui wawancara langsung menggunakan kuesioner dan dianalisis menggunakan analisis bivariat dengan SPSS Versi 22.0. Ibu haml yang patuh terhadap protokol kesehatan untuk pencegahan COVID-19 di wilayah urban dan rural yaitu 91.8%, dan 89.4%, secara berurutan. Sedangkan ibu hamil yang memiliki pengetahuan yang baik mengenai pencegahan terhadap penyakit COVID-19 di wilayah urban dan rural yaitu 54.1% dan 60.4%, secara berurutan. Pengetahuan berhubungan dengan kepatuhan ibu hamil di urban (p=0.020; OR:0.23; 95% CI:0.06-0.82). Sedangkan di wilayah rural, pengetahuan tidak berhubungan dengan kepatuhan ibu hamil (p0.05). Sosialisasi mengenai pentingnya kepatuhan protokol kesehatan tetap perlu dilakukan untuk mencegah paparan penyakit infeksi khususnya COVID-19.